Simultaneous Determination of Caffeine and Pyridoxine in Energy Drinks using Differential Pulse Voltammetry at Glassy Carbon Electrode Modified with Nafion® - Nawar, Amir Shaaban Farag Moham; Pravcová, Kateřina; Česlová, Lenka; Vytřas, Karel; Sýs, Milan (Wiley-VCH, 2019)
A new voltammetric method for simultaneous determination of caffeine and pyridoxine present in different types of commercial energy drinks has been developed. This electroanalytical method is based on anodic oxidation of these biologically active nitrogen-containing heterocycles at glassy carbon electrode covered with thin layer of sulfonated fluoropolymer Nafion® using differential pulse voltammetry in 0.1 M Britton-Robinson buffer of pH 4.5 at potential step 5 mV, potential amplitude 70 mV, and scan rate 50 mV/s. Linear ranges for caffeine and pyridoxine determination were 63.1-600 µM and 7.5-200 µM with the detection limits of 18.9 and 2.2 µM, respectively. It was validated using high-performance liquid chromatography with spectrophotometric detection. Obtained results have shown that voltammetric approach is very simple and low-cost analytical method which can be used for routine determination of caffeine and pyridoxine in energy drinks.
Simultánní stanovení kofeinu a pyridoxinu v energetických nápojích pomocí diferenciální pulzní voltametrie na elektrodě ze skelného uhlíku modifikované Nafionem (R)
Keywords: Caffeine; pyridoxine; glassy carbon electrode; Nafion®; differential pulse voltammetry; energy drinks; Kofein; pyridoxin; elektroda ze skelného uhlíku; Nafion®; diferenciální pulzní voltametrie; energetické nápoje